A comparative cross-sectional study on evaluation of carotid artery intima-media thickness in patients of psoriasis vulgaris: an early predictor of subclinical atherosclerosis - Kannan, Rajkumar; Daniel, Samuel J.; Ashraf A., Mohideen; A., Ramesh; Kumar, Parimalam; Priya B., Yuva (International Journal of Research in Dermatology, 2022)
Background: Psoriasis is associated with atherosclerosis and increased cardiovascular risk. Carotid artery intima-media thickness (CIMT) is used as a non-invasive marker in the assessment of subclinical atherosclerosis. In this study, by using a doppler ultra-sonogram, subclinical atherosclerosis in patients with psoriasis was evaluated in need of special follow-up to reduce cardiovascular morbidity. It was aimed to evaluate the mean CIMT, determine the prevalence of subclinical atherosclerosis and to evaluate the association between the severity, duration of psoriasis and CIMT. Methods: A hospital-based cross-sectional study was done on 25 patients with psoriasis and age, gender, and body mass index (BMI) matched 25 healthy controls over 2 months. CIMT was measured using a doppler ultra-sonogram. Results: Compared to the controls, patients had higher CIMT. 24% of patients had subclinical atherosclerosis compared to 12% of controls. Chronic smokers with psoriasis had a significant association with subclinical atherosclerosis. Because of the COVID-19 pandemic, it was unable to determine the severity and prognosis of subclinical atherosclerosis through follow up. Conclusions: This study provides an insight into the higher prevalence of subclinical atherosclerosis in psoriasis patients, smokers in particular. CIMT can serve as an important noninvasive marker to assess cardiovascular risk.